THE IMPORTANCE OF USING MODERN PEDAGOGICAL TECHNOLOGIES IN FOREIGN LANGUAGE TEACHING - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article aims to highlight the role of using modern technology in teaching English as a second language. It discusses different approaches and techniques which can assist English language students to improve their learning skills by using technology. Among these techniques are online English language learning web sites, computer assisted language learning programs, presentation software, electronic dictionaries, chatting and email messaging programs, listening CD-players, and learning video-clips.